Knowhere to run : starring Star-Lord - Wyatt, Chris, 1975- (Mighty Marvel chapter book., 2017)
A shapeshifter is loose on Knowhere with a weapon capable of blowing up whole planets. Captain Marvel arrives on the space station and recruits Peter Quill, better known as Star-Lord, to help her, on the condition he doesn't tell any of the Guardians of the Galaxy--they might be the shapeshifter, after all.